2014
DOI: 10.1517/17460441.2014.924923
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical development of regorafenib for the treatment of colorectal cancer

Abstract: In order to better predict the efficacy of kinase inhibitors and to utilize them more efficiently, our understanding of drug discovery, the approaches for kinase profiling, and technologies needed for their development are paramount. Indeed, the authors believe that the field should better explore the use of predictive biomarkers that might be able to better assess these therapeutics. Pharmaceutical scientists must also consider the cost effectiveness of the targeted agents developed as a number of the drugs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…38 Sorafenib and regorafenib, which are being evaluated in phase III trials, have shown partial activity against this pathway. 50,51 The PI3K/AKT/mTOR pathway controls cell survival, as well as proliferation and cellcycle regulation. This pathway is activated by various tyrosine kinase receptors, such as EGFR or insulinlike growth factor receptor 1 (IGFR), and by inactivation of the tumour suppressor phosphatase and tensin homo logue (PTEN).…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…38 Sorafenib and regorafenib, which are being evaluated in phase III trials, have shown partial activity against this pathway. 50,51 The PI3K/AKT/mTOR pathway controls cell survival, as well as proliferation and cellcycle regulation. This pathway is activated by various tyrosine kinase receptors, such as EGFR or insulinlike growth factor receptor 1 (IGFR), and by inactivation of the tumour suppressor phosphatase and tensin homo logue (PTEN).…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…The current standard treatment for patients with CRC is surgical resection followed by chemotherapy, e.g., the combination of 5-fluorouracil, oxaliplatin and irinotecan for those patients; however, resistance to chemotherapy remains a major problem in the treatment of this disease because continuous chemotherapy with or without a targeting drug inevitably induces toxicity to normal tissues [2-4]. Despite considerable advances in the treatment of CRC, substantial changes in treatment strategies are required to overcome these problems of drug resistance and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Regorafenib (BAY 73‐4306) is an orally bioavailable, small‐molecule multikinase inhibitor of VEGFR1‐3, TIE2, PDGFR‐β, FGFR, KIT, RET, and BRAF (Miura et al ., ; Wilhelm et al ., ). As efficacy and safety were demonstrated in colorectal cancers and gastrointestinal stromal tumors (GISTs), regorafenib was recently approved for the treatment of patients with metastatic colorectal cancer and advanced GIST by the FDA in 2012 (Miura et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Regorafenib (BAY 73‐4306) is an orally bioavailable, small‐molecule multikinase inhibitor of VEGFR1‐3, TIE2, PDGFR‐β, FGFR, KIT, RET, and BRAF (Miura et al ., ; Wilhelm et al ., ). As efficacy and safety were demonstrated in colorectal cancers and gastrointestinal stromal tumors (GISTs), regorafenib was recently approved for the treatment of patients with metastatic colorectal cancer and advanced GIST by the FDA in 2012 (Miura et al ., ). Clinical trials assessing regorafenib in the treatment of gastric cancer, colorectal cancer, renal cell carcinoma, and hepatocellular carcinoma are underway as monotherapy as well as in combination with other chemotherapeutic agents such as 5‐fluorouracil, oxaliplatin, and irinotecan (Bruix et al ., ; Eisen et al ., ; Li et al ., ; Pavlakis et al ., ).…”
Section: Introductionmentioning
confidence: 99%